PENGARUH MEDIA PEMBELAJARAN INTERAKTIF TERHADAP HASIL BELAJAR KBGT DI SMKN 1 PADANG - Syaiful Bahri; Yasdinul Huda (Universitas Negeri Padang, 2019)
In this research, it is done that is improving student learning outcomes. In observations carried out, the low student learning outcomes in engineering workshops and engineering drawings at SMK Negeri 1 Padang. This study aims to determine whether there is an influence on the results of interactive media learning on the engineering workshops and engineering drawings class X TAV SMK Negeri 1 Padang Academic Year 2018/2019. Sampling is the experimental class X TAV A using interactive media and the X control class TAV B does not use interactive media. The final post-test data collection technique is then analyzed for homogeneity, normality test and hypothesis test. The results of the experimental class obtained an average value of 77.8, while the control class obtained an average value of 74. The results of the calculation of the hypothesis at the significance level α = 0.05 were obtained tcount> t table is (2.75> 1.677), because tcount > table, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. Interacktive media provides a greater increase in learning outcomes which is 5.13%. It can be concluded that interactive media is better than not using interactive media.Keywords: Learning outcomes, interactive media, and engineering workshops and engineering drawings.